Decoration of carbon nanotubes in the substrate or selective layer of polyvinyl alcohol/polysulfone thin-film composite membrane for nanofiltration applications - Mahdie Safarpour; Niloofar Fathi Majd; Samira Jabbarvand Behrouz; Samira Arefi-Oskoui; Alireza Khataee (Results in Chemistry)
Nanofiltration (NF) membranes demonstrate considerable promise for desalinating saline water and wastewater containing mineral salts to overcome the lack of fresh water and improve drinking water quality. This research work aims to detect the influence of carbon nanotubes (CNTs) on the filtration performance of polyvinyl alcohol (PVA)/polysulfone (PSf) thin-film composite NF membranes. For this purpose, CNTs were incorporated in the PSf substrate/PVA selective layer to fabricate a thin-film composite (TFC) with nanocomposite substrate (nTFC) and a thin-film nanocomposite (TFN) membranes, respectively. To fabricate TFC membranes, PSf substrates with different concentrations (16–20 wt%) were made using the phase inversion technique. Then, the selective layer of PVA was formed on the PSf support through cross-linking with glutaraldehyde during dip-coating. The membranes’ NF performance was assessed by filtration of NaCl and Na2SO4 solutions at a relatively low pressure of 0.3 MPa. The salt rejection of all prepared membranes followed the sequence of Na2SO4 > NaCl, indicating the characteristics of negatively charged membranes. By embedment of 0.05 wt% CNT in the PSf substrate/PVA selective layer, the rejections of over 43% for NaCl and over 80% for Na2SO4 were obtained, which is higher than that of TFC-16 as a control membrane (18.1% for NaCl and 74.7% for Na2SO4). Furthermore, in the presence of CNTs, the permeance and fouling resistance of the nTFC and TFN membranes have been improved compared to the TFC-16 membrane.